Research Progress of Liver Cancer Recurrence Based on Energy Metabolism of Liver Cancer Stem Cells - Wu M; Wang H; Wu X; Zeng H; Miao M; Song Y (Journal of Hepatocellular Carcinoma)
Mingming Wu,1,2,* Huayu Wang,2,3,* Xiangxiang Wu,1,2 Huahui Zeng,1,2 Mingsan Miao,1,2 Yagang Song1,2 1Academy of Chinese Medical Sciences, Henan University of Chinese Medicine, Zhengzhou, Henan, 450046, People’s Republic of China; 2Collaborative Innovation Center of Research and Development on the Whole Industry Chain of Yu-Yao, Zhengzhou, Henan, 450046, People’s Republic of China; 3College of Pharmacy, Henan University of Chinese Medicine, Zhengzhou, Henan, 450046, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yagang Song, Academy of Chinese Medical Sciences, Henan University of Chinese Medicine, Zhengzhou, Henan, 450046, People’s Republic of China, Tel/Fax +86-0371-65962546, Email songyagang1016@163.comObjective: The aim of this study is to investigate the recurrence and progression of liver cancer by focusing on the energy metabolism of liver cancer stem cells.Methods: A comprehensive literature search was conducted using databases including CNKI, PubMed, Wanfang, and Citexs to analyze the etiology and treatment of hepatocellular carcinoma (HCC), the factors and mechanisms contributing to HCC recurrence, and the impact of energy metabolism in HCC stem cells on the development of HCC. Furthermore, the association between HCC recurrence and the energy metabolism of HCC stem cells was examined.Results: The primary targets associated with the glycolytic metabolism of HCC stem cells included HK2, PFK, PK, LDH, among others. Glutamine metabolism primarily involves the tricarboxylic acid (TCA) cycle, with main targets such as mTORC1 and reactive oxygen species (ROS). The principal pathway in lipid metabolism is fatty acid (FA) biosynthesis, with key targets being fatty acid synthase (FASN), acetyl-coenzyme A carboxylase (ACC), stearoyl-coenzyme A desaturase-1 (SCD1), and adenosine monophosphate-activated protein kinase (AMPK). Targets in the oxidative phosphorylation pathway include PGC1a. Finally, key targets in iron metabolism encompass System Xc, glutathione peroxidase 4 (GPX4), and DMT1.Conclusion: The glycolytic metabolism of HCC stem cells represents a primary metabolic pathway in HCC stem cells, with key targets including HK2, PFK, PK, and LDH warranting closer attention. Glutamine metabolism should focus on the TCA cycle and targets such as mTORC1 and ROS. Lipid metabolism pathway involves FA biosynthesis, with significant targets being FASN, ACC, SCD1, and AMPK. Iron metabolism, specifically System Xc, GPX4, and DMT1 targets, should be carefully considered. Therefore, interventions for the prevention and treatment of liver cancer recurrence should be directed towards these aspects of liver cancer stem cells.Keywords: liver cancer recurrence, liver cancer stem cells, energy metabolism